Rural Public Service Innovation: Database Training Using Google Apps and Microsoft Office as a Solution for Service Quality Improvement - Zulvia, Yolandafitri; Sari, Devni Prima; Agustina, Dina (Fakultas MIPA Universitas Negeri Padang, 2024)
Innovation in public services is an important aspect in improving the quality of services to the community, especially at the village level. One innovation that is very relevant is the use of Google Apps and Microsoft Office.Pangkalan Koto Baru is one of the villages located in Lima Puluh Kota Regency, West Sumatra Province. From the initial survey conducted by the PKM team, several problems related to administrative services were found, including the lack of skills, knowledge and information and communication technology, data management and administrative information. For this reason, the PKM team conducted Database training activities using Google Apps and Microsoft Office to improve village administrative services. The method used is to provide training and assistance in building an integrated and effective system in managing data and information. This activity ended with an evaluation. Based on the results of observations and evaluations during the activity, there was an increase in the understanding and ability of village officials regarding the use of Google Apps and Microsoft Office to improve services to the community.